MicroRNA-21 Is a Versatile Regulator and Potential Treatment Target in Central Nervous System Disorders - Bai, Xue; Bian, Zhigang (Frontiers in Molecular Neuroscience, 2022)
MicroRNAs (miRNAs) are a class of endogenous, non-coding, single-stranded RNAs with a length of approximately 22 nucleotides that are found in eukaryotes. miRNAs are involved in the regulation of cell differentiation, proliferation, invasion, apoptosis, and metabolism by regulating the expression of their target genes. Emerging studies have suggested that various miRNAs play key roles in the pathogenesis of central nervous system (CNS) disorders and may be viable therapeutic targets. In particular, miR-21 has prominently emerged as a focus of increasing research on the mechanisms of its involvement in CNS disorders. Herein, we reviewed recent studies on the critical roles of miR-21, including its dysregulated expression and target genes, in the regulation of pathophysiological processes of CNS disorders, with a special focus on apoptosis and inflammation. Collectively, miR-21 is an extraordinarily versatile regulator in the progression of CNS disorders and could be a promising biomarker and therapeutic target for these diseases. An in-depth understanding of the mechanisms by which miR-21 affects the pathogenesis of CNS disorders could pave the way for miR-21 to serve as a therapeutic target for these conditions.